2001
DOI: 10.1074/jbc.m011651200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Recruitment of the Mammalian Mediator Subunit TRAP220 by Estrogen Receptors ERα and ERβ

Abstract: Estrogen receptors (ERs) associate with distinct transcriptional coactivators to mediate activation of target genes in response to estrogens. Previous work has provided multiple evidence for a critical role of p160 coactivators and associated histone acetyltransferases in estrogen signaling. In contrast, the involvement of the mammalian mediator complex remains to be established. Further, although the two subtypes ER␣ and ER␤ appear to be similar in regard to principles of LXXLLmediated coactivator binding to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
85
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(93 citation statements)
references
References 69 publications
7
85
1
Order By: Relevance
“…TRAP220 has also been reported to interact with ER␣, although this appears to be relatively weak (18,19,29,30). Recent reports have demonstrated that TRAP220 interacts more strongly with ER␤ (30,50). In addition, data from other studies have suggested that sequences flanking the core motif also influence NR binding specificity (30, 34 -39).…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…TRAP220 has also been reported to interact with ER␣, although this appears to be relatively weak (18,19,29,30). Recent reports have demonstrated that TRAP220 interacts more strongly with ER␤ (30,50). In addition, data from other studies have suggested that sequences flanking the core motif also influence NR binding specificity (30, 34 -39).…”
mentioning
confidence: 89%
“…DISCUSSION TRAP220/DRIP205/PBP was identified as a consequence of its strong ligand-dependent binding to Class II NRs such as TR␣/␤, VDR, and PPAR␥. In contrast, several groups have shown that the interaction of TRAP220 with ER␣ is comparatively weak (18,19,30,51). In this study we compared the interactions of TRAP220 proteins with Class I and Class II NRs using yeast two-hybrid and GST pull-down experiments.…”
Section: Fig 4 the Extended Trap220 Lxm1 Core Motif Exhibits Selectmentioning
confidence: 99%
See 1 more Smart Citation
“…As PBP (Zhu et al, 1997), TRAP220 (Yuan et al, 1998a;Ito et al, 1999) and DRIP205 directly interacted, through two di erentially preferred LXXLL regions (Ren et al, 2000), with distinct hormoneactivated nuclear receptors: i.e. thyroid hormone receptor (THR), vitamin D receptor (VDR), retinoic acid receptor alpha (RARa), retinoic X receptor (RXR), RORa , PPARg (Kodera et al, 2000) and glucocorticoid or estrogen receptors (Burakov et al, 2000;Warnmark et al, 2001). Thus, PBP/TRAP220/DRIP205 acted as bridging co-activators of the basal transcription machinery .…”
mentioning
confidence: 99%
“…This property adds a new function to RB18A, which was previously shown to regulate the activity of physiological promoters, as Bax, p21Waf1 and IGF-BP3, only through its interaction with p53wt (Frade et al, 2000). While the exact mechanisms through which RB18A regulates MDM2 promoter remain unknown, the following points should be taken into account: (a) in preliminary experiments, using electrophoretic mobility shift assay, we could not detect any speci®c binding of RB18A recombinant protein on MDM2 promoter (data not shown); (b) RB18A, being a member of the TRAP220/DRIP205/PBP family, could act as cofactor of the transcriptional machinery by interacting with multiple partners and consequently modulating di erently distinct promoters (Frade et al, 2000;Ito et al, 1999;Atkins et al, 1999;Kodera et al, 2000;Burakov et al, 2000;Warnmark et al, 2001). This is well illustrated by the apparent discrepancy in RB18A properties in di erently regulating p53-dependent apoptosis: indeed, while we herein demonstrated that RB18A activated MDM2 promoter and consequently inhibited p53-dependent apoptosis, we previously demonstrated that RB18A, by acting as p53-cofactor, activated Bax promoter, this activation triggering an increase in p53-dependent apoptosis (Frade et al, 2000).…”
mentioning
confidence: 99%